Analisis Tindak Tutur Direktif dalam Podcast Denny Sumargo Edisi Maret 2025 - Hardiyanti, Lutfi; Astuti, Cutiana Windri; Munifah, Siti (STKIP PGRI Ponorogo Press, 2025)
This study examines directive speech acts in the March 2025 edition of Denny Sumargo's YouTube podcast, focusing on the forms and functions of speech acts that emerge in the interactions between the host and guest stars. This study used a qualitative descriptive method with listening, note-taking, and transcription techniques. Data analysis was carried out through reduction, presentation, and drawing conclusions using Searle's theory. The results of the study indicate that directive speech acts were found in the form of requesting, ordering, advising, suggesting, and demanding. In both episodes, the dominant directive forms were suggesting and advising. These findings indicate that directive speech acts function not only to convey the speaker's intentions but also to build interpersonal rselationships, reflect attitudes, and create a more lively communication atmosphere in the podcast. Keywords: Directive Speech Acts, Pragmatics, Podcast, Denny Sumargo, Indonesia